2022
DOI: 10.3390/brainsci12081088
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-Operative Duration of Symptoms: The Most Important Predictor of Post-Operative Efficacy in Patients with Degenerative Cervical Myelopathy

Abstract: Objective. To explore the most important predictors of post-operative efficacy in patients with degenerative cervical myelopathy (DCM). Methods. From January 2013 to January 2019, 284 patients with DCM were enrolled. They were categorized based on the different surgical methods used: single anterior cervical decompression and fusion (ACDF) (n = 80), double ACDF (n = 56), three ACDF (n = 13), anterior cervical corpectomy and fusion (ACCF) (n = 63), anterior cervical hybrid decompression and fusion (ACHDF) (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The proposed MRI morphometrics significantly correlated with clinical scores (mJOA & CSA ratio: ρ=-0.29, p-value=0.004), better than the manually derived aMSCC (mJOA: ρ=0.09, p-value=0.4) and aSCOR (mJOA: ρ=-0.13, p-value=0.2). Previous studies reported no correlation between manual MRI morphometrics and mJOA 2729 , or correlation for some morphometrics (compression ratio, MCC, and MSCC) with mJOA 12,30 . This could be caused by several factors including differences in cohort sizes and inclusion/exclusion criteria, variability in scanner field strengths (1.5T vs. 3.0T) and sequences used (axial vs. sagittal; T1w vs T2w), and intra– and inter-rater variability in manual measurements.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The proposed MRI morphometrics significantly correlated with clinical scores (mJOA & CSA ratio: ρ=-0.29, p-value=0.004), better than the manually derived aMSCC (mJOA: ρ=0.09, p-value=0.4) and aSCOR (mJOA: ρ=-0.13, p-value=0.2). Previous studies reported no correlation between manual MRI morphometrics and mJOA 2729 , or correlation for some morphometrics (compression ratio, MCC, and MSCC) with mJOA 12,30 . This could be caused by several factors including differences in cohort sizes and inclusion/exclusion criteria, variability in scanner field strengths (1.5T vs. 3.0T) and sequences used (axial vs. sagittal; T1w vs T2w), and intra– and inter-rater variability in manual measurements.…”
Section: Discussionmentioning
confidence: 87%
“…Only a few studies have used automatic or semi-automatic measures to compute spinal cord morphometrics 5,16,17,[31][32][33] . The majority of the studies measured the AP diameter on the midsagittal slice 1,12,29,[34][35][36] . However, the mid-sagittal slice may not correspond precisely to the middle of the spinal cord due to patient scoliosis and/or sequence positioning.…”
Section: Comparison Of Manual Vs Automatic Mri Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 A recent study also concluded that duration of symptoms was an independent risk factor for post-operative efficacy, and that when the duration of symptoms was greater than 6.5 months, the prognosis was likely to be poor. 19 The reasons for this delay are multi-faceted. The diagnostic pathway usually begins with primary care physicians, and while delayed patient presentation likely contributes, delayed detection due to the variability of clinical presentation and the lack of knowledge of cervical cord compression signs and symptoms plays a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses suggest that the C6-7 HU value was affected by disease time. Gou et al [24] suggest that the duration of symptoms was an independent risk factor for poor post-operative e cacy in patients with degenerative cervical myelopathy. Another study showed that intervertebral disc degeneration is related to osteopenia of adjacent vertebrae [25].…”
Section: Discussionmentioning
confidence: 99%